Building information modelling (BIM) capability and delivery success on construction projects. Issue 2 (28th February 2019) - Mahamadu, Abdul-Majeed; Mahdjoubi, Lamine; Booth, Colin; Manu, Patrick; Manu, Emmanuel
Abstract : Purpose: In spite of emerging research on building information modelling (BIM) capability assessment, there is a general dearth of knowledge about the links between often pre-emptive capability measurement attributes and actual delivery success. More so, current studies have not considered success from the wider construction supply chain (CSC) perspective. So far, the perceived importance of capability metrics is not based on post-project evaluations of their contribution to BIM delivery success. This paper aims to identify relevant BIM capability attributes used for qualifying CSC organisations for projects and further aims to investigate their relative importance and influence on some key aspects of BIM delivery success. Design/methodology/approach: Based on heretofore validated set of BIM capability attributes from semi-structured interviews and a Delphi study, a survey of CSC firms on BIM-enabled projects was used to model the influence of BIM capability attributes on BIM delivery success. Multiple regression modelling was performed to ascertain the nature of the relationship between BIM capability attributes and the key aspects of BIM delivery success as identified from the literature. Findings: BIM staff experience and the suitability of proposed methodology prior to project commencement were identified as the most influential on BIM delivery quality, as well as delivery within schedule and on budget. Conversely, the administrative and strategic-level capacities were found as the most influential in leveraging collaboration, coordination or integration of the CSC on projects through BIM. Originality/value: This study provides a step change in prioritising BIM capability criteria based on evidence of their contribution to delivery success in key performance areas, rather than their perceived importance as capability metrics as widely practised.